The cosmos of duty Henry Sidgwick's Methods of ethics - Crisp, Roger 1961- (Oxford University Press, 2015)
Roger Crisp presents a comprehensive study of Henry Sidgwick's 'The Methods of Ethics', a landmark work first published in 1874. Crisp argues that Sidgwick is largely right about central issues in moral philosophy: the metaphysics and epistemology of ethics, consequentialism, hedonism about well-being, and the weight to be given to self-interest